Repeatability, Reproducibility, and Age Dependency of Dynamic Scheimpflug-Based Pneumotonometer and Its Correlation With a Dynamic Bidirectional Pneumotonometry Device. Issue 1 (January 2015) - Bak-Nielsen, Sashia; Pedersen, Iben Bach; Ivarsen, Anders; Hjortdal, Jesper
Abstract : Purpose: To assess the repeatability, reproducibility, and age dependency of dynamic Scheimpflug-based pneumotonometry (Corvis)–generated parameters and their correlation with dynamic bidirectional pneumotonometry device [Ocular Response Analyzer (ORA)] measurements [corneal hysteresis (CH) and corneal resistance factor (CRF)]. Methods: Eyes of 29 healthy participants between 20 and 30 years old were measured using Corvis and ORA. Measurements were performed twice in a row and repeated after 1 week. Repeatability and reproducibility were examined by calculating intraday and interday coefficients of variation (CVs). Corvis measurements were compared with measurements from 19 participants older than 65 years. Results: The most repeatable and reproducible Corvis-generated parameters, with intraday and interday CVs < 10% were as follows: intraocular pressure (IOP), pachymetry, time to first and second applanation (A1 time, A2 time), radius and amplitude at highest concavity (HC radius and HC deformation amplitude, respectively), time to highest concavity (HC time), deflection length and amplitude at highest concavity [HC deflection length and HC deflection amplitude (millimeter), respectively], and time to highest deflection amplitude [HC deflection amplitude (millisecond)]. However, 7 of 19 analyzed parameters showed CVs > 10%. HC-related parameters showed significant age dependency. The correlation between Corvis and ORA was weak (A2 time and CH, r = 0.36, A1 time and CRF, r = 0.41). Corvis-derived IOP was on average 2.2 ± 2.3 mm Hg higher than cornea-compensated IOP, with large differences in patients with high-average IOP. Conclusions: The considerable variation in repeatability and reproducibility should be taken into account when using the Corvis. Corvis parameters showed poor correlation with CH and CRF obtained by ORA measurements.